Unfinished music - Kramer, Richard, 1938- (Oxford University Press, 2008)
Preface. I: First Things. 1. Language and the Beginnings of Creation. Preamble. A Rhetoric of Sonata. Sketches and the Improvisatoyr. Fragments/Patrimonies. II: Emanuel Bach and the Allure of the Irrational. 2. Carl Philip Emanuel Bach and the Aesthetics of Patricide. 3. The Ends of Veranderung. 4. Late Works. Kenner and Liebhaber. A Last Sonata. 5. Probestuck. 6. Diderot's Paradoxe and Emanuel Bach's Empfindungen. III: Between Enlightenment and Romance. 7. Haydn's Chaos and Herder's Logos. 8. Beethoven and the Romance of Creation. Beethoven's Sketches and Shakespeare's Lovers. Sketching the I.